Anticorrosion activity of amoxicillin on mild carbon steel in 1 M hydrochloric acid solution - Đinh, Tuấn; Trần, Xuân Mậu; Nguyễn , Minh Thông; Phạm, Cẩm Nam (Hue University Journal of Science: Natural Science, 2021)
The corrosion inhibition of amoxicillin (AMO) on mild carbon steels in 1 M HCl acid solution was studied experimentally and with computational chemistry techniques. The inhibition efficiency increases with the concentration of AMO, reaching the maximal value (84.72%) at 100 mg·L–1 and 25°C. Several quantum chemical parameters were calculated based on the optimal configuration of AMO at the theoretical level of B3LYB/6-31+G(d,p). Molecular dynamics and Monte Carlo simulation were used to configure the most robust absorption configuration on the surface of Fe(110) and clarify the mechanism of the inhitition process. The results show that AMO is an effective corrosion inhibitor.